2017
DOI: 10.1080/00365521.2017.1310291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing survival in patients with severe acute pancreatitis

Abstract: Bacteremia, high Ranson score, DM, and lower BMI were closely associated with mortality in patients with SAP. When patients with SAP show evidence of bacteremia or diabetes, aggressive treatment is necessary. For the prediction of disease mortality, the Ranson score might be a useful tool in SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Nutrients 2021, 13, 43 2 of 10 Studies in adults have shown that extremes of nutritional status (both undernutrition and obesity) are associated with adverse clinical outcomes and mortality among patients with AP [15,16]. In a recent meta-analysis, obesity has been recognized as an independent risk factor for organ failure in adults with AP [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients 2021, 13, 43 2 of 10 Studies in adults have shown that extremes of nutritional status (both undernutrition and obesity) are associated with adverse clinical outcomes and mortality among patients with AP [15,16]. In a recent meta-analysis, obesity has been recognized as an independent risk factor for organ failure in adults with AP [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most AP are often self-limiting. However, about 20% of cases are clinically severe [2]. Globally, in-hospital mortality rate of patients with severe acute pancreatitis (SAP) are estimated to be 5%-42% [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The modified criteria have a max score of 10. Five parameters are assessed on admission and the other 5 at the 48-hour mark [6][7][8].…”
Section: Introductionmentioning
confidence: 99%